2022
DOI: 10.3171/2021.10.jns212205
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical versus endovascular treatment of craniocervical junction arteriovenous fistulas: a multicenter cohort study of 97 patients

Abstract: OBJECTIVE Craniocervical junction (CCJ) arteriovenous fistulas (AVFs) are treated using neurosurgical or endovascular options; however, there is still no consensus on the safest and most effective treatment. The present study compared the treatment results of neurosurgical and endovascular procedures for CCJ AVFs, specifically regarding retreatment, complications, and outcomes. METHODS This was a multicenter cohort study authorized by the Neurospinal Society of Japan. Data on consecutive patients with CCJ AV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…In a recent multicenter study in patients with CCJ AVFs, embolization was found to be the main risk factor for ischemic complications [ 64 ]. In this cohort, surgical and endovascular approaches were compared, and the results showed a clear advantage for surgical treatment, both in the success rate and in the number of complications [ 65 ]. Similarly, when the endovascular treatments of dural AVFs of the foramen magnum (FM AFVs) and CCJ AVFs were compared, the latter had a lower rate of occlusion and more ischemic complications [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent multicenter study in patients with CCJ AVFs, embolization was found to be the main risk factor for ischemic complications [ 64 ]. In this cohort, surgical and endovascular approaches were compared, and the results showed a clear advantage for surgical treatment, both in the success rate and in the number of complications [ 65 ]. Similarly, when the endovascular treatments of dural AVFs of the foramen magnum (FM AFVs) and CCJ AVFs were compared, the latter had a lower rate of occlusion and more ischemic complications [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the experience of previous studies, microsurgery and interventional embolization were optional treatment strategies for CCJ AVFs. Nevertheless, like AVFs in other parts of the spinal cord, microsurgery was favored for CCJ AVFs, and it usually resulted in better outcomes (5,11,(16)(17)(18)(19). According to the treatment experience of our center, the angioarchitecture of CCJ AVFs was the key to our choice of treatment strategies.…”
Section: Treatment and Outcomesmentioning
confidence: 99%
“…In a recent multicenter study, the complications' overall incidence was 26% (25/97). Ischemic complications were the most common complications, and the associated risk factors were interventional embolization (OR: 4.3, 95%CI: 1.1-16, p = 0.030) and spinal arterial feeders (OR: 3.8, 95%CI: 1.03-14, p = 0.045) (19,22). In treating CCJ AVFs with complex angioarchitecture, it was necessary to carefully identify the blood vessels to avoid ischemic events, especially during interventional embolization.…”
Section: Treatment and Outcomesmentioning
confidence: 99%
“…Recently, neurosurgery has been reported to result in better treatment outcomes than endovascular treatment. 1 A sufficient understanding of the angioarchitecture and accurate diagnosis of CCJ AVF is crucial for safe and complete surgical elimination but is often difficult due to the complex angioarchitecture of this lesion despite recent advances in angiography.…”
mentioning
confidence: 99%